2017
DOI: 10.1590/1806-9282.63.08.685
|View full text |Cite
|
Sign up to set email alerts
|

Flexible ureterorenoscopy in position or fusion anomaly: Is it feasible?

Abstract: Objective: To analyze the results of flexible ureterorenoscopy (F-URS) with holmium laser in the treatment of kidney stones with ectopic and fusion anomalies (horseshoe kidney and rotation anomalies). Method: We reviewed data from 13 patients with fusion and ectopic renal anomalies that underwent F-URS from April 2011 to April 2017. We analyzed demographic and clinical data (age, gender, BMI, anatomical abnormality, location and dimension of the renal calculi) and perioperative data (method of treatment, stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…When reviewing the literature, Eryildirim et al retrospectively evaluated the results of RIRS they carried out on 50 cases with horseshoe kidneys [15] . Astolfi et al performed RIRS on 13 patients with fusion and ectopic renal anomalies [16] . In both studies, RIRS was indicated as a safe and feasible choice for the treatment of kidney stones in patients with renal ectopic and fusion anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying renal anomaly was HSK (n = 204), EK (n = 117), MR (n = 86), cross fused ectopia (n = 2) and others (n = 4). The majority of these studies (n = 13) were retrospective with just one prospective study [26] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…While semirigid URS was used in 41 (10%) cases, FURS was used in 90% of cases. Of the reported studies, a preoperative stent was reported in 26.4% (range 12.4-84.6%, 40/136 patients) [13][14][15][24][25][26]. Placement of ureteral access sheath (UAS) was reported in 11 studies [13-19, 21, 22, 24, 25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation